2014
DOI: 10.1111/codi.12573
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic intersphincteric resection for low rectal cancer: comparison of stapled and manual coloanal anastomosis

Abstract: Laparoscopic intersphincteric resection with a stapled coloanal anastomosis is technically feasible and is less likely to result in anastomotic leakage and stricture formation than a hand-sewn anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
3
29
0
4
Order By: Relevance
“…Many previous studies have been reported which describe satisfactory outcomes in terms of oncological safety, morbidity and low levels of defaecatory dysfunction . The overall mortality rate reported in the literature for taTME/TATA is 0.8%, and the morbidity rate is approximately 25% . Early complications include anastomotic leakage, wound infection, bleeding, ileus, bowel obstruction, urinary infection, lung atelectasis and pelvic sepsis.…”
Section: Introductionmentioning
confidence: 98%
“…Many previous studies have been reported which describe satisfactory outcomes in terms of oncological safety, morbidity and low levels of defaecatory dysfunction . The overall mortality rate reported in the literature for taTME/TATA is 0.8%, and the morbidity rate is approximately 25% . Early complications include anastomotic leakage, wound infection, bleeding, ileus, bowel obstruction, urinary infection, lung atelectasis and pelvic sepsis.…”
Section: Introductionmentioning
confidence: 98%
“…This procedure involves resection of part of, or the entire, internal sphincter and restoration of bowel continuity while obtaining sufficient distal margins. Laparoscopic ISR is associated with less surgical trauma, improved immediate postoperative outcomes and shorter recovery times compared with conventional open surgery, but similar long‐term oncological outcomes. Laparoscopy offers an optimal pelvic dissection with the visceral pelvic fascia remaining intact, and an enhanced view deeper within the pelvis than in the open technique.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although the cohort included both patients who had a stoma at the time of initial surgery and those in whom it was performed as part of an emergency procedure there was no difference in the risk of recurrent leakage between these groups. Previous studies have suggested that hand‐sewn coloanal anastomosis shows a higher incidence of anastomotic stricture than stapled CAA . However, in an updated Cochrane review of nine randomized controlled trials with a total of 1233 patients (622 stapled and 611 hand‐sewn) with colorectal anastomosis, Neutzling et al .…”
Section: Discussionmentioning
confidence: 99%